ENTRE A TEORIA E A PRÁTICA: USO DE CONHECIMENTOS VERNACULARES INDÍGENAS NA ARQUITETURA - Carneiro, Ana Carolina; Piza, João; Saft, Juliana (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
"Vernacular architecture" or "popular architecture" is the one that is characteristic of a country or region, the result of the interaction between climate, materials available and the culture of a certain society. Inserting itself into the discussion of sustainable development, vernacular constructions are mainly in harmony with the environment and maintain a healthy dialogue with the region's climate. Its materials duration over the building life cycle contribute to decrease the total energy expenditure and provide to the end user the necessary thermal comfort. The Brazilian vernacular architecture is that produced by indigenous peoples without contact with techniques brought by the colonizer. Due to the extensive Brazilian territory, there is a variety of indigenous typologies that were studied from the point of view of thermal comfort and NBR 15220-3, and served as the basis for project recommendations.